Complete Genome and Characterization Analysis of a Bifidobacterium animalis Strain Isolated from Wild Pigs (Sus scrofa ussuricus) - Tenggang Di; Huan Zhang; Cheng Zhang; Liming Tian; Menghan Chang; Wei Han; Ruiming Qiao; Ming Li; Shuhong Zhang; Guangli Yang (Microorganisms)
Bifidobacterium is a predominant probiotic in animals that is associated with host intestinal health. The protective mechanisms of the Bifidobacterium animalis (B. animalis) strain, specifically those related to functional gene–host interactions in intestinal homeostasis, remain poorly elucidated. This study reports the complete genome sequence and characterization of a B. animalis strain isolated from wild pig feces, which comprised a single circular chromosome (1,944,022 bp; GC content 60.49%) with 1567 protein-coding genes, and the B. animalis strain had certain acid resistance, bile salt resistance, gastrointestinal fluid tolerance, and antibacterial characteristics. Genomic annotation revealed three putative genomic islands and two CRISPR-Cas systems. Functional characterization identified genes encoding carbohydrate-active enzymes (CAZymes) and associated metabolic pathways, indicating that this strain can degrade complex dietary carbohydrates and synthesize bioactive metabolites for gut homeostasis. Although the antibiotic resistance genes were predicted, phenotypic assays demonstrated discordant resistance patterns, indicating complex regulatory networks. This study indicated the genomic basis of Bifidobacterium–host crosstalk in intestinal protection, providing a framework for developing novel probiotic interventions.